2019
DOI: 10.3390/su11164266
|View full text |Cite
|
Sign up to set email alerts
|

Double Screen Innovation: Building Sustainable Core Competence through Knowledge Management

Abstract: How to exploit the precipitated internal and external knowledge to build dynamic capability in the era of big data remains a big challenge for innovation and business sustainability. This paper documents a novel perspective to address this challenge by exploring the double screen innovation knowledge management practice in Commercial Aircraft Corporation of China Ltd. (COMAC). Drawing from the literature on knowledge management and knowledge-based view, this paper elaborates how the new type of knowledge manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Finally, firms operating in the high-tech industry should pay more attention to build up sustainable competitive advantages from strategic assets as early as possible. As shown in this study, compared with non-high-tech firms, high-tech firms' sustainable competitive advantages rely more on strategic assets, such as cutting-edge technology [51] and management know-how [52]. Acquirers in the high-tech industry compensate for their strategic assets deficiencies through international M&As.…”
Section: Practical Implicationsmentioning
confidence: 85%
“…Finally, firms operating in the high-tech industry should pay more attention to build up sustainable competitive advantages from strategic assets as early as possible. As shown in this study, compared with non-high-tech firms, high-tech firms' sustainable competitive advantages rely more on strategic assets, such as cutting-edge technology [51] and management know-how [52]. Acquirers in the high-tech industry compensate for their strategic assets deficiencies through international M&As.…”
Section: Practical Implicationsmentioning
confidence: 85%
“…As the core of relational social capital, trust can reduce concerns related to knowledge dissemination in a changing environment, which will foster reliable and sustainable supplies of knowledge resources and allow firms to carry out innovation projects in accordance with their established schedules [47,58,71]. With mutual trust, the quality of sustainable communication and collaboration between actors will be improved, overcoming the stickiness and ambiguity of knowledge and shortening the time required for each step of the innovation process [72,73]. Thus, we hypothesize: Hypothesis 6 (H6).…”
Section: Hypothesis 5 (H5) the Structural Dimension Of Social Capitamentioning
confidence: 99%
“…Existing research provides abundant evidence that knowledge is an essential resource for enhancing enterprise innovation and financial performance [12]. Ben et al [13] found that obtaining external knowledge is positively related to innovation and financial performance.…”
Section: Review Of the Academic Literature On Innovation Vouchersmentioning
confidence: 99%